Dynamic relationships between body size, species richness, abundance, and energy use in a shallow marine epibenthic faunal community. Issue 2 (28th December 2014) - Labra, Fabio A.; Hernández‐Miranda, Eduardo; Quiñones, Renato A.
<x xml:space="preserve">Abstract</x> This contribution reports the results of a study analyzing the temporal variation in the empirical relationships among body size, species richness abundance and energy use in a shallow marine community. Our study provides new insights into the generality of trivariate macroecological relationships, and their relationship with well studied bivariate patterns in the ecological literature such as the energetic equivalence rule. We show that despite seasonal forcing and community variability, robust trivariate patterns can be observed. <boxed-text content-type="graphic" id="ece31343-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>